Penerapan Analisis SWOT Terhadap Penentuan Strategi Pemasaran (Studi Kasus pada Cinnamonstory.Id) - Riscal, Detty Agustin; Sahbany, Sri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze the business development strategy at Cinnamonstory.id, a gift decoration and wedding offering service that has been established since 2017. The creativity in offering unique decorations for brides and grooms serves as a value-added advantage that differentiates Cinnamonstory.id from its competitors. The research method used is a descriptive method with data collection techniques through observation and interviews. The data obtained is analyzed using SWOT analysis, which includes internal factors (strengths and weaknesses) as well as external factors (opportunities and threats). The results of the analysis show that the strength value (1.75) is greater than the weakness value (1.00), while the opportunity value (1.60) is smaller compared to the threat value (1.85). Based on the calculation results, Cinnamonstory.id is in Quadrant II of the SWOT diagram, which is in a position of strength and threat, with an internal factor value of 0.38 and an external factor value of -0.13. This position indicates that the appropriate strategy for Cinnamonstory.id is a diversification strategy, which involves making changes to address weaknesses and leverage strengths in facing market threats. By understanding its business position through the SWOT matrix, Cinnamonstory.id can take strategic steps in developing its business, such as continuing to innovate, maintaining product uniqueness, keeping prices competitive, seeking new and more economical distributors, and improving service quality to customers.